Prevalence and Effects of Smartphone Use on Academic Performance of Undergraduate Student Nurses: An Analytical Cross-Sectional Study - Azra Mahmood; Muhammad Alamgir Khan; Asghar Khan (Social Medicine)
Smartphones have become a widely used tool for information and communication, and their use for academic purposes is also growing. Usage of smartphones by undergraduates is rising substantially, which can lead to undesirable behavior and may have detrimental effects on academic performance. Objective. To determine the prevalence and effects of smartphone use on academic performance of undergraduate student nurses. Methods. Analytical cross-sectional study was conducted among 187undergraduate student nurses in Islamabad, Pakistan from December 2023to August 2024. Convenience sampling method was used to recruit undergraduate student nurses. Smartphone use was measured through a smartphone addiction scale (SAS). Students’ Cumulative Grade (CGPA)was taken as a measure to evaluate academic achievement. Chi square test was applied to determine association between CGPA and smartphone use. SPSS version 27.0 was used to analyze data. Results. Study comprised of 62.6% female and 37.4% male. Majority students (70.6%) had moderate level of smartphone use. However-value (0.28) suggested that there is no significant effect of smartphone use on academic performance as determined by chi-square test. Analysis of variance showed that there was no significant difference in the group means (F = 0.674, P = 0.419).Participants identified that smartphone use did lead to lightheadedness, blurred vision, missing planned work, and lack of sleep. Conclusion. Further studies need to be conducted on problems highlighted by the student nurses, to assess the ethical implications of smartphone use, to measure what level of smartphone use results in negative implications, and to determine point of addiction clinically.